The Arabic-Turkish Fragments of the Croatian Latinist Writer Bartul Đurđević in the Polish Anti-Tatar Book Alfurkan Tatarski by Piotr Czyżewski (Wilno, 1616/1617) - Temchin, Sergei (Slavistica Vilnensis, 2020)
The article focuses on the small Oriental texts published in Piotr Czyżewski’s Polish anti-Muslim pamphlet Alfurkan tatarski (Wilno, 1616/1617) directed against the local Tatars of the Grand Duchy of Lithuania. These texts consist of a small Arabic-Turkish prayer and the well-known Ottoman prophecy about “The Red Apple” and the expected victory of Christians over the Turks. The author argues that they go back to the Latin-language editions of the Croatian writer Bartul Đurđević/Bartolomej Georgijević (c. 1506 – c. 1566), who, after his return from a long Ottoman captivity, published several books on the Turkish subjects that were translated into many national European languages and disseminated in different editions throughout Western and Central Europe. These editions often contained samples of Ottoman texts accompanied by a parallel Latin translation and Latin-language interpretations of them, as well as small bilingual dictionaries, thus introducing Islam and the Turkish language to Europe. The article demonstrates the widespread prevalence of both Oriental texts (the Arabic-Turkish prayer and the Ottoman prophecy) in the European printed tradition and the presence of interest in them in the Polish-Lithuanian Commonwealth, evidenced by a manuscript copy of the Ottoman prophecy (late 17th century) and the Polish translation of both texts published in 1548 and 1615.